A WS2-gold nanoparticle heterostructure-based novel SERS platform for the rapid identification of antibiotic-resistant pathogens. Issue 5 (9th April 2020) - Pramanik, Avijit; Davis, Dalephine; Patibandla, Shamily; Begum, Salma; Ray, Priyadarshini; Gates, Kaelin; Gao, Ye; Chandra Ray, Paresh
Abstract : The emergence of antibiotic-resistant bacteria is the biggest threat to our society. Abstract : The emergence of antibiotic-resistant bacteria is the biggest threat to our society. The rapid discovery of drug resistant bacteria is very urgently needed to guide antibiotic treatment development. The current manuscript reports the design of a 2D–0D heterostructure-based surface enhanced Raman spectroscopy (SERS) platform, which has the capability for the rapid identification of the multidrug resistant strain of Salmonella DT104 . Details of the synthesis and characterization of the heterostructure SERS platform using a two dimensional (2D) WS2 transition metal dichalcogenide (TMD) and zero dimensional (0D) plasmonic gold nanoparticles (GNPs) have been reported. The current manuscript reveals that the 2D–0D heterostructure-based SERS platform exhibits extremely high Raman enhancement capabilities. Using Rh-6G and 4-ATP probe molecules, we determined that the SERS sensitivity is in the range of ∼10 −10 to 10 −11 M, several orders of magnitude higher than 2D-TMD on its own (10 −3 M) or 0D-GNPs on their own (∼10 −6 to 10 −7 M). Experimental and theoretical finite-difference time-domain (FDTD) simulation data indicate that the synergistic effect of an electromagnetic mechanism (EM) and a chemical mechanism (CM) on the heterostructure is responsible for the excellent SERS enhancement observed. Notably, the experimental data reported here show that the heterostructure-based SERS has the ability to separate a multidrug resistance strain from a normal strain of Salmonella by monitoring the antibiotic–pathogen interaction within 90 minutes, even at a concentration of 100 CFU mL −1 .